Oil Prices and Real Exchange Rate Movements in Oil-Exporting Countries: The Role of Institutions - Johanna Rickne (Research Institute of Industrial Economics (IFN), 2009)
Political and legal institutions affect the extent to which the real exchange rates of oil-exporting countries co-move with the oil price. In a simple theoretical model, strong institutions insulate real exchange rates from oil price volatility by generating a smooth pattern of fiscal spending over the price cycle. Empirical tests on a panel of 33 oil-exporting countries provide evidence that countries with high bureaucratic quality and strong and impartial legal systems have real exchange rates that co-move less with the oil price.
Keywords: F31; H11; Q48; 330; Real Exchange Rate; Commodity Price; Institutions; Development; Ölpreis; Kaufkraftparität; Good Governance; OPEC-Staaten